A Model of Intention to Participate in Parenting Interventions: The Role of Parent Cognitions and Behaviors. Issue 3 (May 2021) - Gonzalez, Carolina; Morawska, Alina; Haslam, Divna M.
Highlights: Parent cognitions and behaviours related significantly to intention to participate. Parents' perceived threat played a significant role in intention to participate. Previous help-seeking behaviours was the strongest link to intention to participate. Efforts to engage parents should prioritise their cognitions and behaviours. Abstract: A wide range of factors, from perceived child behavior problems to sociocultural factors, have been identified as impacting the engagement of parents in parenting interventions. However, parents' cognitions and behaviors have not been evaluated sufficiently to understand their role in initial parental engagement. The current study aimed to examine why some parents are more likely to want to participate in parenting programs and how their cognitions and behaviors are related to their intention to participate in future parenting interventions. We tested the hypothesised model of parental factors on intention to participate using structural equation modelling (SEM) in AMOS. This study ( N = 6, 733) analyzed existing data from the International Parenting Survey (IPS), a web-based tool developed to collect information about parents' views on family and parenting at a population level in several countries. Results showed that parents' coercive parenting, parental consistency, positive encouragement, relationship with their child, parental self-efficacy, psychological distress, and help-seeking behaviors were significantly related to their intention to participate in future parenting interventions. The structural model of parents' cognitions and behaviors explained 16% of the variance in intention to participate. Although the current model explained a small but significant percentage of the variance, it expands existing understanding regarding parental cognitions and behaviors and their relationship to intention. Implications for further research and engagement practice are discussed.